보리순 분말을 첨가한 도토리묵의 품질 특성 - 신미혜(Mee-Hye Shin); 이민호(Min-Ho Lee); 정남용(Nam-Yong Chung) (동아시아식생활학회지, 2020)
This study examined the quality characteristics to evaluate the optimal mixing ratio of barley sprout powder (0%, 2%, 4%, and 6%) in acorn Muk. The moisture contents of acorn Muk increased significantly (76.13~91.73%) with increasing amount of barley sprout powder. The L, a, and b values of the Hunter’s color values decreased significantly with increasing amount of barley sprout powder. The DPPH radical scavenging activities (9.63~11.38%) and ABTS radical scavenging activities (61.07~80.55%) of acorn Muk were significantly higher in the groups with barley sprout powder than in the group without barley sprout powder. In the physical properties, the hardness, cohesiveness, and chewiness of acorn Muk decreased significantly in proportion to the amount of barley sprout powder. The acorn Muk containing 4% barley sprout powder showed a high score with regard to flavor, moistness, chewiness, and overall acceptance. These results suggest that the appropriate amount of barley sprout powder for making acorn Muk is 4%. Moreover, acorn Muk added with barley sprout powder had the highest functional component and antioxidant activity. KCI Citation Count: 5